Institutional externalities and actor performance in polycentric governance systems. (29th August 2018) - Mewhirter, Jack; Lubell, Mark; Berardo, Ramiro
Abstract: This article examines the relationship between institutional externalities and an actor's ability to achieve their goals in the decision‐making forums that exist in polycentric governance systems. We argue that an actor's performance is largely a function of the transaction costs associated with participation in a variety of forums. Institutional externalities—instances where the decisions made in one forum impact another forum—may increase or decrease transaction costs in linked forums, subsequently impacting actor performance. Using survey data collected from forum participants in the California Delta and Tampa Bay watershed governance systems, we examine how the strength of perceived externalities generated between linked forums affects an individual's perceived performance in the forum receiving the externality. We find that externalities are prevalent in both systems, but have varying effects on performance. Externalities, on average, negatively impact actor performance in the California Delta, but neither increase nor decrease performance in Tampa Bay. Further analyses reveal that in both systems, the effect of externalities on performance in the externality‐receiving forum is largely conditional on their performance in the externality‐generating forum. Externalities are negatively associated with forum performance when actors exhibit low levels of performance in the externality‐generating forum. The negative effect is mitigated when actors exhibit higher levels of performance in the externality‐generating forum.